Lentiviral RNAs can use different mechanisms for translation initiation. (22nd July 2008) - Ricci, Emiliano P.; Rifo, Ricardo Soto; Herbreteau, Cécile H.; Decimo, Didier; Ohlmann, Théophile
Abstract : The full-length genomic RNA of lentiviruses can be translated to produce proteins and incorporated as genomic RNA in the viral particle. Interestingly, both functions are driven by the genomic 5′-UTR (5′-untranslated region), which harbours structural RNA motifs for the replication cycle of the virus. Recent work has shown that this RNA architecture also functions as an IRES (internal ribosome entry site) in HIV-1 and -2, and in SIV (simian immunodeficiency virus). In addition, the IRES extends to the gag coding region for all these viruses and this leads to the synthesis of shorter isoforms of the Gag polyprotein from downstream initiation codons. In the present study, we have investigated how different members of the lentivirus family (namely HIV-1 and -2, and SIV) can initiate protein synthesis by distinct mechanisms. For this, we have used the competitive reticulocyte lysate that we have recently described. Our results show that HIV-1 is able to drive the synthesis of the Gag polyprotein both by a classical cap-dependent mechanism and an IRES, whereas HIV-2 and SIV appear to use exclusively an IRES mechanism.